Enhancing Boardroom Diversity in Saudi Arabia - Abdullah Eskandarany (Enhancing Boardroom Diversity in Saudi Arabia, 2023)
This monograph contains an evaluation of the research dealing with the drivers and significance of corporate board diversity and corporate governance focused on Saudi Arabia. It specifically shows how to increase board diversity in a different culture and social setting. This is achieved by presenting more than two thousand items of secondary data and comparing these to data from 2020 to show the social change from the old to new diversity logics amidst the more general social change, with comparative analysis of global trends. The book will provide a clear picture of boardroom diversity in Saudi Arabia. This will contribute to knowledge through understanding board diversity and exploring whether there have been changes in the boardroom due to social structure shifts, and the extent of resistance. It will benefit both accounting and governance academics as well as the broader practitioner community. Furthermore, it will be important for those looking at social change and the role of the Saudi national plan Vision 2030 which provides a strategic framework to reduce the country's dependence on oil, diversify its economy and develop its public sector. The first book to investigate boardroom diversity in Saudi Arabia Captures the change of Saudis boardroom in six demographic types of diversity Looks into the impact of social settings in Saudi culture by highlighting the Vision of 2030 Provides a comprehensive review of Saudi Arabia's most recent corporate governance codes
10.1515/9783110741735; 10.1515/9783110741735